PENGARUH BAURAN PEMASARAN, CELEBRITY ENDORSER DAN GAYA HIDUP TERHADAP KEPUTUSAN PEMBELIAN SEPEDA MOTOR MEREK HONDA BEAT - Tengku Putri Lindung Bulan; Muhammad Rizal; Wahyu Akbar (Jurnal Manajemen Inovasi, 2019)
AbstractThis study aims to determine the influence of marketing mix, celebrity endorser and lifestyle on purchasing decisions a Honda Beat motorcycle brand at the Faculty of Economics, Samudra University students. The number of samples in this study amounted to 96 respondents. Data analysis method used is multiple linear regression analysis and proof of hypothesis using the analysis of the coefficient of determination, t test and F test. The regression model obtained in this study is Y = 3,677 + 0,116X1 + 0,261X2 + 0,506X3. From the analysis of the coefficient of determination it can be explained that the marketing mix, celebrity endorser and lifestyle influence the decision to purchase a Honda Beat motorcycle brand at the Faculty of Economics, University of Samudra by 46.1%, while the remaining 53.9% is influenced by other variables not examined in the study, this is like product attributes, brand image and so on. From the t test, it is known that the marketing mix has insignificant influence on purchasing decisions, celebrity endorser has a significant influence on purchasing decisions and lifestyle has a significant influence on purchasing decisions. From the results of the F test it is known that the marketing mix, celebrity endorser and lifestyle simultaneously have a significant influence on purchasing decisions a Honda Beat brand motorcycle at the Faculty of Economics, Samudra University students. KeywordsMarketing Mix, Celebrity Endorser, Lifestyle, Purchasing Decisions